Sincerely, the duke - Grey, Amelia (Grey, Amelia. Say I do, 2024)
"Miss Edwina Fine has one shot at finding a husband before the ton learns her secret. With red hair, green eyes and being one of triplets, she knows the superstitions and rumors about women like her. So when a marriage proposal from the Duke of Stonerick arrives by mail, Edwina jumps at the chance to solve her problems. But nothing could prepare her for the attraction that sparks between them when they finally meet. It will take more than Edwina's wit to navigate her past, reservations about marriage and the passion that ignites within her for the irresistible duke. Rick, Duke of Stonerick, enjoys his life exactly as it is: honing his expert marksmanship, playing cards and fencing with his friends. He even enjoys exchanging affectionate humor with his mother about his lack of matrimonial engagement. But when a recurring illness reminds Rick he has no heir, he picks a name from the list of prospects his mother presents and writes a simple marriage proposal. Then he forgets about it--until that very lady with an iron will and breathtaking bravery shows up at his doorstep, ready to accept. Edwina tempts him like no other and suddenly, marriage doesn't seem much of an inconvenience after all. But will keeping his illness a secret cost him her love?"--